Experimental study on preparation and thermal storage properties of expanded graphite/paraffin wax as a shape-stabilized phase change material. (November 2022) - Li, Yang; Fu, Zaiguo; Xue, Mingxing; Shao, Zhixiong; Li, Yan; Zhu, Qunzhi
Abstract: As an organic phase change material (PCM), paraffin wax (PW) has the problem of low thermal conductivity. It has been applied in the heat storage engineering. To improve the thermal performance of paraffin wax adopted in heat storage, it was mixed with expanded graphite (EG) via melt-blending method. The EG/PW was compressed into a shape-stabilized phase change material (SSPCM). The DSC curve was measured and the relationship between pressure and density of the SSPCM was tested. The SSPCM was vacuum encapsulated in aluminum bags and placed in a packed bed heat storage system to measure the thermal storage properties. The results showed that the thermal conductivity of the SSPCM was 7.06 W/(m °C), and the maximum density of the SSPCM was 1.07 g/cm 3 . The average thermal efficiency of the heat storage system was 95.3%. The number of heat storage units was positively correlated with the heat release power. This study explored the feasibility of a simplified heat storage system.